Teaching Digital Sustainability in Higher Education from a Transdisciplinary Perspective - Thomas J. Lampoltshammer (MDPI AG, 2021)
Sustainability is gaining importance in society, government, and the economy, particularly during today’s rapidly changing environment, due to digitalization and digital transformation. Awareness, as well as systematic and critical thinking, are crucial to address the great societal challenges postulated within the SDGs, and thus should be reflected in contemporary education. Consequently, higher educational institutions face a high level of responsibility to prepare their students properly. Postgraduate programmes for professional training, in particular, have great potential, as the in-depth work experience of students can be leveraged to engage with them as co-leaders towards sustainable solutions in the digital age, from a transdisciplinary perspective. Thus, this paper introduces a teaching framework for digital sustainability in higher education under the light of transdisciplinarity. The framework and its inherent methods are discussed, followed by an exploratory analysis, covering the experiences of over 100 students over the course of two years in a postgraduate master’s programme. We present the results of the students’ learning and ideation process towards digital products/services to tackle challenges within the SDGs. In addition, we provide a critical reflection of prerequisites for teaching the framework, challenges experienced during teaching, and potential solutions, as well as ideas towards the future expansion of the framework.